2018
DOI: 10.1017/wet.2018.70
|View full text |Cite
|
Sign up to set email alerts
|

Pyroxasulfone Is Effective for Management ofBromusspp. in Winter Wheat in Western Canada

Abstract: In response to concerns about acetolactate synthase (ALS) inhibitor-resistant weeds in wheat production systems, we explored the efficacy of managing Bromus spp., downy and Japanese bromes, in a winter wheat system using alternative herbicide treatments applied in either fall or spring. Trials were established at Lethbridge and Kipp, Alberta, and Scott, Saskatchewan, Canada over three growing seasons (2012)(2013)(2014) to compare the efficacy of pyroxasulfone (a soil-applied very-long-chain fatty acid elongase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Enhanced monitoring of downy brome populations will comprise a critical mitigation measure to limit the spread of glyphosate-resistant downy brome in Alberta as well as neighboring provinces and states. While effective pre-and post-emergence herbicide options 25,26,48,49 will play an important role in managing glyphosate-resistant downy brome, integration of non-chemical management strategies will be necessary to mitigate selection for resistance to these remaining herbicide options. Growing competitive cultivars 50 , crop rotations involving summer-annuals 51,52 , strategic timing of nitrogen fertilization 53 , and judicious use of tillage 54 may help reduce selection pressure for herbicide-resistant downy brome in cropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced monitoring of downy brome populations will comprise a critical mitigation measure to limit the spread of glyphosate-resistant downy brome in Alberta as well as neighboring provinces and states. While effective pre-and post-emergence herbicide options 25,26,48,49 will play an important role in managing glyphosate-resistant downy brome, integration of non-chemical management strategies will be necessary to mitigate selection for resistance to these remaining herbicide options. Growing competitive cultivars 50 , crop rotations involving summer-annuals 51,52 , strategic timing of nitrogen fertilization 53 , and judicious use of tillage 54 may help reduce selection pressure for herbicide-resistant downy brome in cropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…Through cross-and multiple-herbicide resistance testing, some selective herbicides used in wheat fields cannot effectively distinguish them. In the field study by Johnson et al [6], treatment with pyroxsulam and flucarbazone-sodium obtained a similar result, in which these two kinds of ALS inhibitors were still effective. Therefore, in wheat fields, in addition to ALS inhibitors, other MOA herbicides (such as PS II and ACCase inhibitors) may not be effective for weed control.…”
Section: Discussionmentioning
confidence: 72%
“…When the density of B. japonicus in wheat fields is 4 plants per square meter, it can cause yield losses of 2.11% to 2.24% [5]. Thus, the grain and biological yields of wheat varieties are negatively affected by competition from B. japonicus [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical for spring wheat to be free of weeds that can interfere with this crop. For sustainable wild mustard control, the integration of POST and -PRE herbicide application is recommended [25]. For instance, Johnson et al [9] reported a broad spectrum weed suppression can be attained through the use of tribenuron and pyroxsulam which are both ALS inhibiting active ingredients.…”
Section: Resultsmentioning
confidence: 99%